(untitled) (Global Journal of Human-Social Science, 2021)
Based on Halliday s theory of Grammatical Metaphor in Systematic Functional Linguistics SFL this paper delves into the distribution features as well as interpersonal meanings of modality metaphor in discussion section of Linguistics Research Articles RAs The discussion sections of 60 RAs in Applied Linguistics 2016-2020 were selected and the classification of explicit subjective modality metaphor from Halliday Matthiessen Huang and Fan was adopted in current study The results show that epistemic modality metaphors take up the highest proportion in explicit subjective modality metaphor 84 8 followed by boulomaic evaluative and evidential modality metaphors The reasons for this discrepancy are explained from the scientificity and objectivity of academic discourse and the multiple interpersonal meanings of epistemic modality in terms of raising different or supplementary viewpoints in a conciliatory way and strengthening negotiation between writers and readers